IMPACT OF ACCIDENTS ON THE SUSTAINABLE DEVELOPMENT OF A MINING COMPANY - Uktam, Norenov; Carsten, Drebenstedt (FUDMA JOURNAL OF SCIENCES, 2026)
Industrial accidents constitute a persistent impediment to sustainable mining, systematically disrupting the interconnected economic, social, and environmental dimensions of mining operations. Despite considerable scholarship addressing mine safety and sustainable development independently, the relationship between these domains remains insufficiently theorized, with existing literature offering only fragmented perspectives on how accident dynamics shape long-term sustainability performance at the organizational level. This study addresses that gap through a systematic qualitative review of peer-reviewed academic literature, institutional reports, and case-based empirical sources encompassing mining accidents, safety culture, emergency response, and sustainable development frameworks. Employing thematic analysis, the paper synthesizes current knowledge on the principal determinants of mining accidents and examines the mechanisms through which such accidents affect each pillar of sustainability. The review demonstrates that accident consequences are fundamentally systemic: deficiencies in safety management precipitate operational disruption and financial losses, erode worker well-being and community trust, and exacerbate long-term environmental risk. The study contributes theoretically by integrating accident causation frameworks with sustainability outcomes within a unified analytical perspective, establishing that accident prevention must be reconceptualized not merely as an operational function but as a strategic precondition for sustainable mining practice. The findings indicate that effective safety culture, preventive maintenance, workforce training, emergency preparedness, and organizational learning are critical determinants of risk reduction and long-term resilience. Overall, the realization of sustainable mining is contingent upon the systematic embedding of accident prevention within broader corporate management and sustainability governance frameworks.